Penggunaan Metode Analisis Tugas dalam Meningkatkan Kemampuan Bina Diri Berpakaian Seragam pada Anaktunagrahita Sedang di SLB YPAC Manado - Marice Kowaas (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study is to get a clear picture of the use of task analysis methods in overcoming the problem of children's inability to wear uniforms. This research originated from the observations that the researchers carried out at SLB YPAC Manado, especially in grade 3 SD, that there was a mentally retarded child who could not wear his own clothes and still needed help from others. The task analysis method is a method of a series of sequential small steps that are used to help make it easier to solve a problem and can minimize mistakes that are repeated from children. This study used experimental research in the form of Single Subject Research (SSR), with the A - B - A research design. The subject of the study was a mentally retarded child in grade III SD who could not wear uniforms. The results showed that the use of the task analysis method can improve the ability of self-development in uniform in mentally retarded children in grade III at SLB YPAC Manado